Structural basis of transcription activation by the global regulator Spx. Issue 18 (16th September 2021) - Shi, Jing; Li, Fangfang; Wen, Aijia; Yu, Libing; Wang, Lu; Wang, Fulin; Jin, Yuanling; Jin, Sha; Feng, Yu; Lin, Wei
Abstract: Spx is a global transcriptional regulator in Gram-positive bacteria and has been inferred to efficiently activate transcription upon oxidative stress by engaging RNA polymerase (RNAP) and promoter DNA. However, the precise mechanism by which it interacts with RNAP and promoter DNA to initiate transcription remains obscure. Here, we report the cryo-EM structure of an intact Spx-dependent transcription activation complex (Spx–TAC) from Bacillus subtilis  at 4.2 Å resolution. The structure traps Spx in an active conformation and defines key interactions accounting for Spx-dependent transcription activation. Strikingly, an oxidized Spx monomer engages RNAP by simultaneously interacting with the C-terminal domain of RNAP alpha subunit (αCTD) and σ A . The interface between Spx and αCTD is distinct from those previously reported activators, indicating αCTD as a multiple target for the interaction between RNAP and various transcription activators. Notably, Spx specifically wraps the conserved –44 element of promoter DNA, thereby stabilizing Spx–TAC. Besides, Spx interacts extensively with σ A through three different interfaces and promotes Spx-dependent transcription activation. Together, our structural and biochemical results provide a novel mechanistic framework for the regulation of bacterial transcription activation and shed new light on the physiological roles of the global Spx-family transcription factors.